EMERGENCE OF PAN-INDIAN SOUTH CINEMA: DECONSTRUCTING THE COMPOSITIONAL ELEMENTS AND NARRATIVE PARADIGMS - Putta, Santhosh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research delves into the phenomenon of Pan-Indian South cinema, focusing on deconstructing its compositional elements responsible for its transformative success on the Pan-Indian Landscape, distinguishing itself from the Bollywood cinema, which was previously synonymous with Indian Cinema globally Rajadhyaksha & Willmen (2012). Bollywood long dominated the scholarly discourse on Indian cinema, leading to a notable gap in understanding the nuanced dynamics of South Indian regional Cinema’s and its ascent to the popularity on the pan-Indian Stage. This study addresses this gap by examining how Pan-Indian South Cinema, exemplified by landmark films such as the “Baahubali” series, “Robo 2.0,” "K.G.F. 1," "K.G.F. 2," and “R.R.R." navigates and celebrates its diverse regional identities while resonating with audiences across diverse linguistic and cultural boundaries present in India. Utilizing a methodological approach that integrates textual and content analysis, this research looks at the compositional elements and other factors that contributed to the success of these films on the Pan-Indian stage. The study elucidates the intrinsic factors contributing to Pan-Indian South cinema’s success and enduring appeal through a critical lens. By combining innovative cinematic practices and merging the cast of regional and Bollywood Cinema, Pan-Indian South cinema has emerged as a new hybrid cinema, offering audiences narratives often rooted in local cultures and traditions of south India, yet resonating with the Pan-Indian audience. The findings of this inquiry not only enrich our understanding of Pan-Indian Cinema but also shed light on the complexities of cinematic productions and creative choices crucial for their success. Ultimately, this research contributes to a more comprehensive appreciation of India’s diverse cinematic traditions and underscores Pan-Indian South Cinema’s significance as a vibrant, hybrid and influential force in contemporary Indian Cinema.